2005
DOI: 10.1080/14703290500291842
|View full text |Cite
|
Sign up to set email alerts
|

Teaching reflection to nursing students: a qualitative study in an Irish context

Abstract: Teaching nursing students to reflect on their practice is now officially considered an essential component of nursing education in a number of countries. The aim of this study was to explore nurse teachers' perceptions and experiences of using reflection with diploma nursing students in an Irish context. One of the central themes to emerge, upon which this article is based, is the manner in which reflection is actually taught and/or facilitated by nurse educators in diploma nursing programmes, and the factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
5
0
1
Order By: Relevance
“…The process of developing and evaluating RP mechanisms for nurses is ongoing (Bailey & Graham ; Boucher ; Forneris & Peden‐McAlpine ), however to date, research has predominantly been in nursing education (Ferrari ; Glaze ; Gould & Masters ; O'Connor & Hyde ; Paget ), as opposed to the clinical setting. A number of authors have identified that specific skills need to be developed for effective reflection to occur (Boud et al .…”
Section: Literature Reviewmentioning
confidence: 99%
“…The process of developing and evaluating RP mechanisms for nurses is ongoing (Bailey & Graham ; Boucher ; Forneris & Peden‐McAlpine ), however to date, research has predominantly been in nursing education (Ferrari ; Glaze ; Gould & Masters ; O'Connor & Hyde ; Paget ), as opposed to the clinical setting. A number of authors have identified that specific skills need to be developed for effective reflection to occur (Boud et al .…”
Section: Literature Reviewmentioning
confidence: 99%
“…While reflective practices have been shown to be effective for learning, allowing students to mentally review and clarify their own thinking and feelings (Pavlovich 2007), they are time-consuming for students and can be difficult for teaching staff to monitor (O'Connor and Hyde 2005;Yeh 2006). Reflective journals may facilitate only limited dialogue between teachers and students about their feedback, especially in large classes.…”
Section: Introductionmentioning
confidence: 97%
“…Models of reflective practice (Schön 1987) apply across many professional contexts (Connaughton and Edgar 2011), including the health professions such as nursing, psychology, physiotherapy and medicine (Haffling et al 2010). Schön's conceptualisation of reflection as falling into three stages, namely conscious reflection, criticism and action, has influenced the incorporation of reflective journal entries (Boud 2001;Boyd 2002;O'Connor and Hyde 2005) or group discussion processes (Platzner, Blake, and Ashford 2000) into university curricula.…”
Section: Introductionmentioning
confidence: 99%
“…Being reflective is increasingly recognized as a highly appropriate and significant strategy in nurse education. Subsequently, skills in reflection are developed as a core component in many undergraduate and postgraduate nursing programs [9,10] . Theorists describe reflection as an active and purposeful cognitive process which juxtaposes individual beliefs and knowledge with evidence to inform practice development [11,12] .…”
Section: Literaturementioning
confidence: 99%